Xenopus laevis oocyte maturation is affected by metal chlorides. Issue 5 (August 2015) - Marin, Matthieu; Slaby, Sylvain; Marchand, Guillaume; Demuynck, Sylvain; Friscourt, Noémie; Gelaude, Armance; Lemière, Sébastien; Bodart, Jean-François
Highlights Cadmium (CdCl2) inhibits progesterone (Pg)-induced oocyte maturation. Metal chlorides, specially zinc, induce oocyte maturation independently of Pg. Cadmium and lead chlorides affect calcium signaling. Deregulation of oocyte maturation could affect oocyte fertilization. Xenopus laevis oocyte shows a great sensitivity to cadmium and lead.